Palladium-promoted [2+2+2] cocyclization of arynes and unsymmetrical conjugated dienes: synthesis of justicidin B and retrojusticidin B - Patel, Ramesh M.; N. P. Argade (Organic Letters, 2013)
A facile synthesis of natural and unnatural arylnaphthalenes has been demonstrated via the unprecedented palladium-promoted [2 + 2 + 2] cocyclization of arynes and unsymmetrical conjugated dienes using the N-heterocyclic carbene as a ligand. The unsymmetrical dienes used herein are actually alpha-coupled acrylate - cinnamate combinations bearing two beta-positive carbons and follow the key [2 + 2 + 2] cocyclization pathway.